Characterization of Modular Join-Semilattices - Talukder, MR; Arif, MHB (GANIT: Journal of Bangladesh Mathematical Society, 2011)
In this paper we have proved a classical characterization of modular join-semilattices. We have also given some characterizations of modular ideals of join-semilattices through congruences. Key words: Join-semilattices; modular semilattices; distributive semilattices; quotient semilattices GANIT J. Bangladesh Math. Soc. (ISSN 1606-3694) 29 (2009) 43-49 DOI: http://dx.doi.org/10.3329/ganit.v29i0.8514